Nutritional Value of Selected Wild Edible Mushrooms from Nepal - Sapkota, Merina; Jha, Sanjay Kumar (Tribhuvan University Journal, 2025)
Present study aims to identify and evaluate nutritional properties and mineral content of two wild edible mushrooms Cantharellus subligaria's, and Laccaria proxima. The samples were collected during the monsoon season in April to August 2022 from National zoological garden, Suryabinayak, Bhaktapur, Nepal. Following collection, the samples were thoroughly cleaned to remove any debris and properly labeled. Eight parameters were analyzed such as macro nutrients like protein, fat, crude fiber, ash, carbohydrates and minerals including Iron, calcium, and Phosphorus. All macro and minerals compositions were determined on a dry weight basis. The moisture content of mushrooms varied from 9.43-10.32%, ash 14.01-14.38%, carbohydrate 50.75-56.82%, fat 1.34-1.38%, protein 17.9-21.52% and fiber 33.76-42.53%. The minerals content of mushroom samples ranged whereas Calcium 171-249.97% The examined wild edible mushrooms (Cantharellus subcibarius and Laccaria proxima) exhibit elevated levels of protein, fiber, and minerals relative to numerous produced varieties, rendering them nutritionally superior in certain respects. The practical consequences encompass their potential as a sustainable, nutrient-dense food source, enhancing food security, bolstering local economies, and fostering additional research on their production and health advantages.